2010
DOI: 10.1158/1078-0432.ccr-09-3030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Telomerase Polymorphism in Non–Small Cell Lung Cancer

Abstract: Purpose: Lung cancer is the leading cause of death in oncologic patients of western countries, with very low survival rates. Telomerase main components are the catalytic subunit (hTERT) and the RNA template (hTR). A functional polymorphism in the hTERT gene was found in the promoter region (−1327T/C), and individuals homozygous for the −1327C/C genotype present shorter telomere length compared with T-carrier genotypes. Our purpose was to investigate the potential prognostic role of the hTERT functional genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…hTERT promotes the proliferation of different types of cancer [1922]. Previously, we observed that hTERT promotes the proliferation and invasion of gastric cancer via interactions with different genes [2325].…”
Section: Introductionmentioning
confidence: 99%
“…hTERT promotes the proliferation of different types of cancer [1922]. Previously, we observed that hTERT promotes the proliferation and invasion of gastric cancer via interactions with different genes [2325].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, human telomerase reverse transcriptase (hTERT), as the rate-limiting step in the activation of telomerase, is known to be an accurate measure of telomerase activity (TA). The presence of hTERT is therefore required for aberrant cell proliferation and carcinogenesis in most cancer types (5). Thus, telomerase is considered to be a potential marker of oncogenesis (6).…”
Section: Introductionmentioning
confidence: 99%
“…As a putative polygenic trait, several loci have been implicated (Vasa-Nicotera et al , 2005; Andrew et al , 2006; Mangino et al , 2008, 2009; Starr et al , 2008; Levy et al , 2010), with some including genes known to be directly involved in telomere maintenance in humans (Codd et al , 2010). In addition to telomerase activity (Ludlow et al , 2008) and telomere length (Matsubara et al , 2006a, b), single-nucleotide polymorphisms (SNPs) located in the TERT - CLPTM1L locus have been associated with exceptional longevity (Atzmon et al , 2010), coronary artery disease (Matsubara et al , 2006a), idiopathic pulmonary fibrosis (Mushiroda et al , 2008), glioma (Shete et al , 2009), red blood cell count (Kamatani et al , 2010), survival in patients with lung cancer (Catarino et al , 2010) and several cancers (Ruiz-Llorente et al , 2007; McKay et al , 2008; Andrew et al , 2009; Broderick et al , 2009; Choi et al , 2009; Hosgood et al , 2009; Landi et al , 2009; Van Dyke et al , 2009; Zienolddiny et al , 2009; Hsiung et al , 2010; Johnatty et al , 2010; Prescott et al , 2010; Shen et al , 2010; Turnbull et al , 2010; Wang et al , 2010). Specifically, relationships have been reported between the C allele of a common, intronic polymorphism in CLPTM1L (rs401681) and shorter telomere length in elderly females (Rafnar et al , 2009), increased PSA levels (Gudmundsson et al , 2010), increased basal cell carcinoma (Rafnar et al , 2009; Stacey et al , 2009), prostate (Rafnar et al , 2009), cervical (Rafnar et al , 2009), bladder (Rothman et al , 2010) and lung (Wang et al , 2008; Rafnar et al , 2009; Kohno et al , 2010; Miki et al , 2010) cancer risk and a reduced risk of melanoma (Stacey et al , 2009) and pancreatic (Petersen et al , 2010) cancer, although there is a lack of association with breast cancer (Rafnar et al , 2009; Pooley et al , 2010).…”
Section: Introductionmentioning
confidence: 99%